Incidence trends of childhood acute lymphoblastic leukemia in Saudi Arabia: Increasing incidence or competing risks?. (August 2020) - Jastaniah, Wasil; Essa, Mohammed F.; Ballourah, Walid; Abosoudah, Ibrahim; Al Daama, Saad; Algiraigri, Ali H.; Al Ghemlas, Ibrahim; Alshahrani, Mohammad; Alsultan, Abdulrahman
Highlights: Incidence of childhood acute lymphoblastic leukemia (cALL) varies between countries. Incidence of cALL was 2.35 in Saudi Arabia (SA) compared to 4.1 in USA per 100, 000. The percent annual increase in the incidence of cALL was 4.58 % in SA vs. 0.7 % in USA. Improved reporting, and timely access-to-care may influence trends in incidence in SA. Abstract: Introduction. The incidence of childhood acute lymphoblastic leukemia (cALL) varies between countries likely as a result of competing risks including infections, access-to-care, socioeconomic influences, and/or ethnicity. However, little is known about disease burden in high-income Arab countries offering free-of-charge healthcare. The hypothesis was that, due to population characteristics (young age, high fertility and parental consanguinity rate), the incidence of cALL in Saudi Arabia is equal or higher than that observed in high-income Western countries. Methods. Saudi databases were used to calculate the incidence of cALL from 2001 to 2014. Incidence trends over time of children with ALL, 14-years of age or younger, were analyzed and compared with those reported in USA. Results. The age-adjusted incidence over the years was lower in Saudi Arabia compared to USA. However, the incidence trend of cALL in Saudi Arabia was increasing at a rate higher than that observed in USA (p < 0.001). The overall incidence of cALL in Saudi Arabia increased from 1.58/100, 000 in 2001 to 2.35/100, 000 population in 2014. The median annual increase was 4.58 %. The incidence in males increased from 1.88 to 2.71/100, 000, and from 1.21 to 1.86/100, 000 population in females. Conclusions. The reported incidence of cALL in Saudi Arabia is rapidly increasing. The increasing trend may reflect evolving socioeconomic structure, improved access-to-cancer care, and improved diagnosis/ reporting capacity. This highlights the need for better understanding of cALL causes and the need for the formation of separate national pediatric cancer registries in different countries to monitor childhood cancer incidence trends.